Basement membrane degradation and inflammation play a role in the pulmonary hemorrhage induced by a P-III snake venom metalloproteinase - Castro Castro, Ana Cristina (2021)
Snakebite envenoming is a neglected tropical disease affecting millions of people every year, especially in vulnerable rural populations in the developing world. Viperid snakes cause envenomings characterized by a complex pathophysiology which includes local and systemic hemorrhage due to the action of snake venom metalloproteinases (SVMPs). The pathogenesis of SVMP-induced systemic hemorrhage has not been investigated in detail. This study explored the pulmonary hemorrhage induced in a murine model by a P-III SVMP from the venom of Crotalus simus. Histological analysis revealed extravasation in the lungs as early as 15 min after intravenous injection of the toxin, and hemorrhage increased at 360 min. Western blot analysis demonstrated the cleavage of basement membrane (BM) proteins in lung homogenates and in bronchoalveolar lavage fluid, implying an enzymatic disruption of this extracellular matrix structure at the capillary-alveolar barrier. Likewise, alveolar edema was observed, with an increment in protein concentration in the bronchoalveolar lavage fluid, and a neutrophil-rich inflammatory infiltrate was present in the parenchyma of the lungs as part of the inflammatory reaction. Pretreatment of mice with indomethacin, pentoxifylline and an anti-neutrophil antibody resulted in a significant decrease in pulmonary hemorrhage at 360 min. These findings suggest that this P-III SVMP induces acute lung injury through the direct action of this enzyme in the capillary-alveolar barrier integrity, as revealed by BM degradation, and as a consequence of the inflammatory reaction that develops in lung tissue. Our findings provide novel clues to understand the mechanism of action of hemorrhagic SVMPs in the lungs.